2009
DOI: 10.1007/s10654-009-9382-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and clustering of metabolic syndrome components in pediatrics

Abstract: This study was performed to determine the risk factor pattern of the metabolic syndrome (MetS) in association with serum nitric oxide metabolites (NO(x)) in children and adolescents. The study included 851 children and adolescents, aged 4-19 years. The MetS was defined according to modified Adult treatment Panel III criteria. Cluster analysis was performed using principle components analysis with varimax orthogonal rotation to examine the risk factor pattern of the MetS. The prevalence of MetS was 10.8 and 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…4,[30][31][32] Our results are consistent with those of Gruber et al, 4 who showed reduced nitrite/nitrate levels (NOx) in juvenile obesity, and with Siervo and Bluck, 32 who showed reduced NO synthesis in obesity and in metabolic syndrome.…”
Section: Discussionsupporting
confidence: 92%
“…4,[30][31][32] Our results are consistent with those of Gruber et al, 4 who showed reduced nitrite/nitrate levels (NOx) in juvenile obesity, and with Siervo and Bluck, 32 who showed reduced NO synthesis in obesity and in metabolic syndrome.…”
Section: Discussionsupporting
confidence: 92%
“…Increased shear stress can stimulate angiogenesis and increase blood flow. NO levels are elevated in diabetic young adults (12) and obese children (21) and linked to glomerular hyperfiltration, oxidative stress, and inflammation, although NO synthesis might later decline with disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is evidence that NO production is suppressed by NOS inhibitors such as asymmetric dimethylarginine (ADMA) [25] and caveolin-1 [26], which are elevated in T2DM. Conversely, others have reported increased plasma nitrate and nitrite concentrations in individuals with T2DM [27,28], which may indicate a quenching of NO activity or upregulation of NO synthesis to counteract resistance. It is possible that dietary nitrate supplementation in this population could ameliorate the impact of T2DM on NOS-dependent NO synthesis by increasing the amount of NO produced via the enterosalivary pathway [14].…”
Section: Introductionmentioning
confidence: 88%